Study on the capability and characteristics of heavy metals enriched on microplastics in marine environment. (July 2019) - Gao, Fenglei; Li, Jingxi; Sun, Chengjun; Zhang, Letian; Jiang, Fenghua; Cao, Wei; Zheng, Li
Abstract: In this study we examined the adsorption characteristics of heavy metals on microplastic through laboratory test and field test. We demonstrated that polyvinyl chloride, polypropylene, polyethylene, polyamides and polyformaldehyde could adsorb lead, copper and cadmium in the simulating solution, and the heavy metals showed higher adsorbance on PVC and PP particles compared with PA, PE and POM. In the field experiment, the adsorption rate and concentration of heavy metals varied significantly among different plastic types and locations. The adsorbability of PP and PVC toward Pb and Mn was strongly correlated with the metal concentration in seawater. We also compared the adsorption quantity of PP to heavy metals and polycyclic aromatic hydrocarbons which resulted in an order of magnitude within one month. During the adsorption, the surface morphology of the microplastics which were washed and corroded by seawater underwent a rough-smooth-rough changing process, and different materials had great differences. Graphical abstract: Unlabelled Image Highlights: Physical properties of microplastics affect its enrichment ability to metals. The adsorbance was related to the metal concentrations and the enrichment time. Microplastics presented selectivity when enriching heavy metals. The aging degree of different microplastics was different in marine environment.